2017
DOI: 10.1007/s00262-017-2005-z
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation-induced upregulation of PD-L1 mediates immune escape in human lung adenocarcinoma

Abstract: It was reported that PD-L1 expression was correlated with genetic alterations. Whether PD-L1 was regulated by mutant Kirsten rat sarcoma viral oncogene homolog (KRAS) in non-small-cell lung cancer (NSCLC) and the underlying molecular mechanism were largely unknown. In this study, we investigated the correlation between PD-L1 expression and KRAS mutation and the functional significance of PD-1/PD-L1 blockade in KRAS-mutant lung adenocarcinoma. We found that PD-L1 expression was associated with KRAS mutation bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(190 citation statements)
references
References 42 publications
9
172
1
1
Order By: Relevance
“…Specific siRNA sequences targeting the EGFR gene (si‐EGFR) were synthetized by Beijing Aoke Peak Biotechnology (Beijing, China). Expression vectors and siRNA transfections were carried out as described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific siRNA sequences targeting the EGFR gene (si‐EGFR) were synthetized by Beijing Aoke Peak Biotechnology (Beijing, China). Expression vectors and siRNA transfections were carried out as described .…”
Section: Methodsmentioning
confidence: 99%
“…Specific siRNA sequences targeting the EGFR gene (si-EGFR) 22,23 were synthetized by Beijing Aoke Peak Biotechnology (Beijing, China).…”
Section: Expression Vectors and Sirna Transfectionmentioning
confidence: 99%
“…Emerging evidence suggests that coexistence of driver mutations in NSCLC is frequently associated with higher PD-L1 expression. Previous studies have shown EGFR mutations [14][15][16], ALK rearrangements [27,28], and KRAS mutations [29] were positively correlated with PD-L1 expression. However, the regulatory mechanism in wild-type EGFR tumors is still unknown.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, in our study, we selected A549 and H460 cell lines, which are both wild‐type for EGFR but have different levels of PD‐L1 expression. To explore the potential regulatory mechanisms of higher PD‐L1 levels in H460 cells, we examined the downstream signaling pathways, as previously reported ; the results showed PD‐L1 upregulation was associated with the activation of STAT3, AKT, and ERK. By inhibiting p‐STAT3, p‐AKT, and p‐ERK, PD‐L1 was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy analyses could be performed in patients with pancreatic or colorectal cancers, because RAS mutations are more frequent in those types of cancers. Furthermore, in lung adenocarcinoma, it has been demonstrated that KRAS mutation induces the expression of programmed death ligand 1 (PD-L1) [23, 24]. Accordingly, combination therapy of Salirasib with an anti-PD-1 agent may enhance the anti-cancer efficacy.…”
Section: Discussionmentioning
confidence: 99%